Notifications of work-related injuries and diseases: an observational study on a mining disaster - Rita de Cássia Costa da Silva; Maykon Anderson Pires de Novais; Paola Zucchi (BMC, 2023)
Abstract Introduction Accidents at work are events that endanger the health and life of workers. They are considered a public health problem, being the object of studies and actions in the Brazilian health system. The collapsed of the ore tailings dam in the municipality of Brumadinho, Brazil, in January 2019, shocked the world due to the proportion of environmental and human damage caused. In this context, concern for the health of workers gained prominence. This paper evaluated the impact of the collapse of the mining tailings dam in Brumadinho, on notifications of occupational health problems before and after the disaster. Methods An observational, longitudinal and retrospective study, of the time series type with a statistical approach was carried out on notifications of work-related injuries and diseases, available in the local database of the Notifiable Diseases Information System between January 2017 and December 2021. Results During the study period, 520 notifications of work-related injuries and conditions were registered. Of this total, 67.3% were serious work accidents, 26.0% mental disorders, 12.3% accidents with biological material and 2.9% repetitive strain injuries/musculoskeletal disorders, occupational dermatoses and induced hearing loss by noise. Occurrences were more frequent in 2019, the year in which the mining disaster occurred, recording 65.2% of total notifications. Regarding the volume of notifications after the disaster, there was a statistically significant reduction (p < 0.001) for accidents with biological material; significant increase for severe work accident and mental disorder. The average time between the occurrence of the injury and the notification showed a statistically significant reduction for accidents involving biological material (p = 0.001) and a significant increase for serious accidents at work (p = 0.016). Conclusions It was demonstrated that there were changes in the number of notifications when comparing the period before and after the mining disaster, with a consequent impact on the health of workers, which may persist over the years.